"Every time I tell my story I learn something new": Voice and inclusion in research with Black women with histories of substance use and incarceration. (September 2022) - Gunn, Alana J.; Hardesty, Melissa; Overstreet, Nicole; Wallace, Scyatta
While current ethical procedures aim to minimize risks to imprisoned individuals, there is heightened awareness of the need to protect those who participate in research post-incarceration while under community-based supervision. Formerly incarcerated women, in particular, face myriad challenges to community reintegration which also make them vulnerable participants in research. As such, this study explores how 28 formerly incarcerated Black women experience the qualitative research process. Findings revealed that women engaged in research because these contexts were viewed as therapeutic spaces for raising awareness that can help others. Moreover, the interview process allowed women to share their pasts in ways that promote their recovery from addiction. Participants also reported risks of emotional distress and fears regarding researcher stigma. The implications for trauma-informed interviewing practices underscore the need for greater considerations of the role of the researcher, research environment, and how they contribute to one's personal recovery.